PLEDOARIE PENTRU MODERNIZARE / INOVARE: REZULTATE NOVATECA 2015 - KULIKOVSKI,Conf. univ., director, Departamentul studii și cercetări, Lidia (BIBLIOPOLIS, 2020)
The modernization / innovation of libraries activity concepts is to introduce a variety in a field library, is to change the competitive fundamentals in a specific field library. We do not have many vibrant, noisy, colorful libraries… but the movement towards the modernization of the field occurred with the support of the Novateca Program. The article is about the fulminant results of the Novateca Program at the level of library professional development, implementation of new services, mentality changing, relation with the community and local administration, partners; and at the level of social/public visibility of modern libraries. The article presents an analysis of weak point identified in the difficult and fascinated processes of library modernization, of the activity innovation model; offers rules, guidelines for modernization and innovation and encourages the monitoring and self-evaluation of management effort in the processes of modernization.